An Evolutionary Classification of Genomic Function - Graur, Dan (Genome Biol Evol, 2015)
The pronouncements of the ENCODE Project Consortium regarding “junk DNA” exposed the need for an evolutionary classification of genomic elements according to their selected-effect function. In the classification scheme presented here, we divide the genome into “functional DNA,” that is, DNA sequences that have a selected-effect function, and “rubbish DNA,” that is, sequences that do not. Functional DNA is further subdivided into “literal DNA” and “indifferent DNA.” In literal DNA, the order of nucleotides is under selection; in indifferent DNA, only the presence or absence of the sequence is under selection. Rubbish DNA is further subdivided into “junk DNA” and “garbage DNA.” Junk DNA neither contributes to nor detracts from the fitness of the organism and, hence, evolves under selective neutrality. Garbage DNA, on the other hand, decreases the fitness of its carriers. Garbage DNA exists in the genome only because natural selection is neither omnipotent nor instantaneous. Each of these four functional categories can be 1) transcribed and translated, 2) transcribed but not translated, or 3) not transcribed. The affiliation of a DNA segment to a particular functional category may change during evolution: Functional DNA may become junk DNA, junk DNA may become garbage DNA, rubbish DNA may become functional DNA, and so on; however, determining the functionality or nonfunctionality of a genomic sequence must be based on its present status rather than on its potential to change (or not to change) in the future. Changes in functional affiliation are divided into pseudogenes, Lazarus DNA, zombie DNA, and Jekyll-to-Hyde DNA.